Diane Goode's Christmas magic : poems and carols (New York : Random House, 1992)
A collection of traditional and modern Christmas poems and carols.
Keywords: Christmas-Juvenile poetry; Carols-Texts-Juvenile literature; Christmas music; Christmas-Poetry; Poetry-Collections; Carols